Efecto de un biorregulador en el desarrollo inicial de varias especies frutales. - García Arteaga, Dilmo José (2017)
The present study was carried out between September 2016 and April 2017 on the Campus of the Polytechnic of Manabí ESPAM. The study evaluated the Effect of a bioregulator on the initial development of several fruit species. It aimed to quantify the initial development of soursop, arazá, mamey and orange. For the purpose, the product Basfoliar Algae was applied. Two treatments were tested: with biostimulant and without biostimulant. The bioregulator was applied as drench at fortnightly intervals (13 applications) in doses of 3 ml/L of water. An amount of 500 ml per plant were applied. The variables evaluated were: plant height, stem diameter, root length, number of roots and plant vigor. Statistical analysis was performed using the t-test for paired samples. The results showed that there was a positive effect of the hormonal biostimulant on soursop for the variables plant height (p <0.01), number of leaves (p <0.01), number of roots (p <0, 01) and plant vigor (p <0.05). For arazá, significant differences were found on root length (p <0.05) and number of roots (p <0.01). There was no effect of the hormonal biostimulant application related to any studied variables for mamey. The application of the hormonal biostimulant in orange showed a positive effect on the vegetative growth of plant height (p <0.05) at 190 days after establishment in field.